Study on the association between Physical growth and Socio-economic condition of North-West and South-West Khasi children in the State of Meghalaya. - Warjri, Dr Barikor C (International Journal of Scientific Research and Management (IJSRM), 2017)
This Paper makes an attempt to understand how the under-nutrition of children is associated with age, sexand certain socio-economic factors. In the study we include 495 girls and 557 boys aged 3 to 18 years inwhich their weight and height were taken and their socio economic status was recorded. Certain socioeconomicvariables were collected and classified arbitrarily into different groups or categories with a view tounderstanding their influence on demographic variables i.e. base on income group, educational level andfamily size. The data collected for the present study were quantified and analyzed statistically, using SPSSWindow software. These variables were considered as risk factors of under-nutrition as indicated by oddsratios derived from logistic regression analysis. The present study has revealed that the prevalence of undernutrition,especially underweight, is significantly associated with household income and parental education. Itis evident that household income is an important factor in influencing the prevalence of stunting in thepresent population. Unlike in the case of underweight and stunting, the effects of socioeconomic factors onwasting are not statistically significant in the present population.